Impact assessment framework of just energy transition: based on the justice principles - Shangguan, Chenyue; Shangguan, Ziheng; Sun, Wen (Frontiers in Environmental Science, 2024)
The concept of a Just Energy Transition (JET) has gained prominence in sustainable development discussion, with impact assessment serving as a key foundation for advancing global energy justice. Currently, the primary assessment frameworks encompass distributional justice, procedural justice, and restorative justice. However, these dimensions exhibit a certain degree of overlap, and a standardized set of metrics for their evaluation remains conspicuously lacking. To address this research gap, this study employs a literature review and logical reasoning to construct a comprehensive framework consisting of four distinct assessment dimensions: cognitive justice, distributional justice, procedural justice, and redistributive justice. The framework delineation the boundaries and logical relationships among these dimensions. This study emphasizes the foundational role of cognitive justice, positioning it as the cornerstone upon which other dimensions of justice rely. Moreover, it puts forth a constructive argument that future generations, as direct beneficiaries, should bear additional responsibility to uphold intergenerational justice. This multi-dimensional framework deepens our understanding of the complexities of JET and encourage critical discourse on the subject.